Tips for Tutoring Improving Reading Abilities. A Guidebook for the Peer Tutor - Slaughter, Judith P. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
Designed to reinforce initial training and to provide a collection of useful ideas for students who serve as peer tutors, this guidebook provides tips for tutors to improve the reading abilities. Following an introduction which asserts the benefits of peer tutoring programs, the guidebook is divided into two major sections: "Tutoring Targets" and "Steps to Success." The first section offers the tutor basic suggestions for establishing positive relationships with tutees, and strategies for teaching and evaluating. Subjects discussed in the first part include tutor characteristics, the learning environment, helpful strategies, and evaluation of the tutoring session. The second section presents activities for improving vocabulary (by using the dictionary, checking the context, and analyzing the parts of words) and reading comprehension (by sizing up, digging in, looking back, and perusing the introduction or preface of a book). The guidebook also discusses highlighting and offering help to students. (Sixteen references are included.) (PRA)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Foreign Countries; Guidelines; Higher Education; Peer Teaching; Reading Comprehension; Reading Improvement; Reading Instruction; Tutorial Programs; Tutoring; Undergraduate Students; Vocabulary Development; Canada -- Peer Coaching; Guides, Classroom -- Teacher